Griffith-like phase in Crednerite CuMnO2. (July 2017) - Shukla, Kaushal K.; Singh, Rahul; Kumar, A.; Ghosh, A.K.; Chatterjee, Sandip
Graphical abstract: Highlights: Ac and dc magnetic measurements have been performed on CuMnO2 . From both the magnetic data the existence of Griffith-like phase (GP) established. The existence of GP has also been confirmed by analyzing magnetic susceptibility which for a Griffith Phase, should be characterized by an exponent less than unity, that is χ(T) ∝(T/TC -1) −(1−λ) where 0 ≤ λ ≤ 1. The GP anamoly in χ' gradually diminishes with the application of small dc field, in accordance with the extreme sensitivity shown by the GP in other compounds. Behavior of χac with the applied magnetic field also supports the existence of Griffith like phase above the AFM order in the present system. The exchange interaction at short bonds is stronger, which, with the uniaxial magnetic anisotropy of Mn 3+, leaves the system frustrated. This frustration may induce the Griffith-like phase. Abstract: Ac and dc magnetic measurements have been performed on CuMnO2 . From both the magnetic data the existence of Griffith-like phase established. Both ac and dc magnetic studies demonstrate aspects of Griffith phase-like behavior. The onset of Griffith like phase is associated with an effective slowing down. The presence of short range ferromagnetic ordering is observed above the antiferromagnetic transition temperature. Different directions in the triangular ab plane in CuMnO2 become inequivalent: there exist for each Mn two short and four long MnMn distances in the plane. The exchange interaction at short bonds is stronger, which, with the uniaxial magnetic anisotropy of Mn 3+ (spins are oriented predominantly along the long MnO bonds), leaves the system frustrated. This frustration may induce the Griffith-like phase.